Analysis of wave spectrum by Blackman-Tukey method and fast fourier method - Le Nguyen , Hoa Tien; Tran Xuan, Dung; Lam Van, Hao; Nguyen Tien, Thanh; Nguyen Hoang, Phong; Vo Luong, Hong Phuoc (Vietnam Journal of Marine Science and Technology, 2021)
Energy of surface waves is almost dissipated as propagating from shallow water to muddy flat and in mangrove forest. The study aims to analyze energy spectral density by using Blackman-Tukey (BT) and Fast Fourier Transform (FFT) methods in order to analyze the wave energy in mangrove areas in Cu Lao Dung (Soc Trang province). BT method is easy to use especially in short time series. Selection of lag number m is very important to determine the energy amount and number of peaks. Whereas, FFT method helps us to analyze the shift of spectral energy as waves propagate into shallower water. The results show that wave energy is dissipated from shallow water to muddy flat and into mangrove forests. The spectral energy shifts from low frequency to higher frequency as propagating into mangrove forests. This can prove the non-linear characteristics of waves in mangrove forests and the complicated hydrodynamic processes in mangrove forests.